Cerebral Modifications and Visual Pathway Reorganization in Maculopathy: A Systematic Review - Nuzzi, Raffaele; Dallorto, Laura; Vitale, Alessio (Frontiers in Neuroscience, 2020)
Background Macular degeneration (MD) is one of the most frequent causes of visual deficit, resulting in alterations affecting not only the retina, but also the entire visual pathway up to the brain areas. This would seem related not just to signal deprivation, but also to a compensatory neuronal reorganization, having significant implications in terms of potential rehabilitation of the patient and therapeutic perspectives. Objective To outline, by analyzing the existing literature, current understanding of brain structural and functional changes detected with neuroimaging techniques in subjects affected by juvenile and age-related maculopathy. Methods Articles using various typologies of central nervous system (CNS) imaging in at least six patients affected by juvenile or age-related maculopathy were considered. A total of 142 were initially screened. Non pertinent articles and duplicates were rejected. Finally, 19 articles, including 649 patients, were identified. Results In these sources, both structural and functional modifications were found in MD subjects’ CNS. Changes in visual cortex grey matter volume was observed both in AMD (age-related) and JMD (juvenile); in particular, an involvement of not only its posterior part, but also the anterior one, suggests further causes besides an input-deprivation mechanism only. White matter degeneration was also found, more severe in JMD than AMD. Moreover, functional analysis revealed differences in cortical activation patterns between MD and controls, suggesting neuronal circuits reorganization. Interestingly, attention and oculomotor training allowed better visual performances and correlated to a stronger cortical activation, even of the area normally receiving inputs from lesioned macula. Conclusions In MD structural and functional changes in cerebral circuits and visual pathway can happen, involving both cerebral volume and activation patterns. These modifications, possibly due to neuronal plasticity (already observed and described for several brain areas) can allow patients to compensate for macular damage, and gives therapeutic perspectives which could be achievable through an association between oculomotor training and biochemical stimulation of neuronal plasticity.